Attracting and Retaining Global Talent: International Graduate Students in the United States - Bhandari, Rajika (International Higher Education, 2018)
In light of current developments in in-bound international student flows to the U.S., this article uses multiple recent data sources to examine the appeal of the U.S. as a destination for international graduate students, as well as the current status of international graduate enrollment in the U.S.